MRI-based iPAGAT polymer gel dosimetry using fast recovery spin echo sequences. (August 2019) - Fujino, K; Ono, K; Hayashi, S; Sasaki, K; Hioki, K; Miyazawa, M; Akagi, Y; Hirokawa, Y
Abstract: In an estimation of iPAGAT polymer gel dosimeters using a magnetic resonance imaging (MRI) system, the dosimetric characteristics were investigated with two echo sequences: a spin echo (SE) and a fast recovery fast spin echo (FRFSE) sequence. FRFSE can shorten total scan time compared to SE because of its short repetition time (TR) and long echo train length (ETL). Although the R2-dose response measured from FRFSE was decreased compared to SE, both responses were fitted quadratic curve with a high correlation coefficient. In addition, their calibrated dose distributions showed high conformity to the planned data in the three-dimensional (3D) gamma index, dose volume histogram (DVH) and surface rendering analyses; however, results of SE were a little superior to FRFSE. In conclusion, it is suggested that FRFSE can present the accurate characteristics of polymer gel dosimeters under the optimum parameters.